2015
DOI: 10.1007/s11121-015-0545-z
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Sensitivity of Measures to Change

Abstract: Little attention is paid in prevention research to the ability of measures to accurately assess change, termed “responsiveness” or “sensitivity to change.” This paper reviews definitions and measures of responsiveness, and suggests five strategies for increasing sensitivity to change, with central focus on prevention research with small samples: (a) Improving understandability and cultural validity, (b) assuring that the measure covers the full range of the latent construct being measured, (c) eliminating redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 47 publications
0
36
0
Order By: Relevance
“…The spiritual domain is especially important at the end of life, but this domain was not often included in existing measurement instruments [28]. For instance, the EORTC QLQ-C15-PAL also did not include certain topics that appear to be relevant for patients in the end of life: Quality of care, Preparation for death, Spirituality or Transcendence [78,90,[104][105][106][107]. The EORTC QLQ-C15-PAL was derived from the EORTC QLQ-C30 and the authors confirmed that existential or spiritual issues were mentioned by health care professionals and some patients as important additional topics to the measurement instrument.…”
Section: Discussionmentioning
confidence: 99%
“…The spiritual domain is especially important at the end of life, but this domain was not often included in existing measurement instruments [28]. For instance, the EORTC QLQ-C15-PAL also did not include certain topics that appear to be relevant for patients in the end of life: Quality of care, Preparation for death, Spirituality or Transcendence [78,90,[104][105][106][107]. The EORTC QLQ-C15-PAL was derived from the EORTC QLQ-C30 and the authors confirmed that existential or spiritual issues were mentioned by health care professionals and some patients as important additional topics to the measurement instrument.…”
Section: Discussionmentioning
confidence: 99%
“…This enhanced granularity in understanding item level functioning allowed in IRT affords more systematic exploration of an under recognized but highly salient consideration in prevention research, related to responsiveness or sensitivity to change, which describes a measure’s accuracy in assessing change in response to intervention. Fok and Henry (2015) persuasively advocate for more routine assessment of responsiveness as a third measurement characteristic that prevention researchers should consider in addition to reliability and validity. The authors present several practical strategies that allow researchers to assess and optimize responsiveness of measurement scales.…”
Section: Refinements In Statistical Applications and Measurement Provmentioning
confidence: 99%
“…Continuing this discussion of alternative designs, Fok, Henry, and Allen (2015) describe the stepped wedge design (SWD) and the interrupted time-series design (ITSD). The SWD is a related design to the DWLD, wherein the timing of the crossover to intervention for each unit is randomized, and power is maximized when each unit has its own randomization step.…”
Section: Use Of Alternative Research Designs That Maintain Rigor Whilmentioning
confidence: 99%
See 1 more Smart Citation
“…Little attention is paid in prevention research to the ability of measures to accurately assess change; this property can be termed “responsiveness” or “sensitivity to change.” Fok and Henry (2015) review definitions and measures of responsiveness, and suggest five strategies for increasing sensitivity to change, with a central focus on prevention research with small samples. These strategies include (a) improving understandability and cultural validity, (b) assuring that the measure covers the full range of the latent construct being measured, (c) eliminating redundant items, (d) maximizing sensitivity of the device used to collect responses; and (e) asking directly about change.…”
Section: Overview Of the Special Sectionmentioning
confidence: 99%